2020
DOI: 10.33073/pjm-2020-052
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Key micro-RNAs and mRNAs under the Hand, Foot, and Mouth Disease Virus Infection

Abstract: To clarify crucial key micro-RNAs and mRNAs associated with hand, foot, and mouth disease (HFMD) virus infection, we conducted this bioinformatics analysis from four GEO datasets. The following datasets were used for the analysis: GSE85829, GSE94551, GSE52780, and GSE45589. Differentially expressed genes (DEGs) were acquired, and the analysis of functional and pathway enrichment and the relative regulatory network were conducted. After screening common differentially expressed miRNAs (DE-miRNAs), five key miRN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…To find miRNAs related to the EV71 infection process, we searched PubMed and found that six miRNAs, including miR-451a, miR-3960, miR-4516, miR-320c, miR-4443, and miR-3665, were significantly differentially expressed in several studies (Supplementary Table S4) [ 27 33 ]. Thus, we regarded these miRNAs as potentially involved in the EV71 infection process.…”
Section: Resultsmentioning
confidence: 99%
“…To find miRNAs related to the EV71 infection process, we searched PubMed and found that six miRNAs, including miR-451a, miR-3960, miR-4516, miR-320c, miR-4443, and miR-3665, were significantly differentially expressed in several studies (Supplementary Table S4) [ 27 33 ]. Thus, we regarded these miRNAs as potentially involved in the EV71 infection process.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account the different courses of disease, different sample collection methods, virus replication, detoxification cycle, individual immune differences and other factors, a single detection method has some limitations and missed or false detected rate. Therefore, in the early stage of HFMD in children or when the immune function is relatively low, the combined detection of nucleic acid RNA and serum IgM antibody is helpful to improve the early detection rate (25,26) and accuracy. Two methods of detection and follow-up are helpful to evaluate the recovery of children: to prevent overtreatment to avoid secondary injury, and to eliminate the excessive worries and worries of children and their families about the disease.…”
Section: Discussionmentioning
confidence: 99%
“…miR-671-5p has also been among miRNAs participating in the pathogenesis of periodontitis through establishment of ceRNA regulatory network regulating autophagy ( Bian et al, 2022 ). miR-671 has also been found to be down-regulated in patients with rheumatoid arthritis ( Tang et al, 2019 ), hand, foot, and mouth disease ( Lin et al, 2020 ), placenta accreta spectrum ( Chen et al, 2020b ), coronary artery disease ( Zhong et al, 2020 ), Parkinson’s disease ( Uwatoko et al, 2019 ) and Kawasaki disease ( Zhang et al, 2018 ). Table 6 shows the detailed information about the role of this miRNA in human diosrders.…”
Section: Non-malignant Conditionsmentioning
confidence: 99%